HUBUNGAN DUKUNGAN ORANG TUA DENGAN MOTIVASI BELAJAR DARING PADA ANAK SMK NEGERI 2 DIMASA PANDEMI COVID-19 DI KABUPATEN TAKALAR: The Relationship Of Parental Support With Online Learning Motivation Of Students Of Vocational School 2 Takalar During The Covid-19 Pandemic - Suardi; Ernawati; Zainuddin; Kamriana; Dewiyanti; Alwi; Ayu Ashari (Media Keperawatan: Politeknik Kesehatan Makassar, 2024)
Background: This virus, which is often referred to as the Covid-19 virus or corona virus, is a large family of viruses which can cause disease in animals or humans. In humans, the corona virus is known to cause respiratory infections ranging from the common cold to more serious diseases such as Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS). Aims: to find out the relationship between parental support and online learning motivation among SMK Negeri 2 children during the Covid-19 pandemic in Takalar Regency. Method: This research is an analytical survey research using a cross sectional research design. The sampling technique is Accedential Sampling. The research location is SMK Negeri 2 in Takalar Regency with a sample size of 69. Data analysis used the chisquare test. Results: Obtained a value of ρ = 0.023 ≤ α (0.05), this shows that Ha is accepted and H0 is rejected. Conclusion: research results show that there is a relationship between parental support and online learning motivation among SMK Negeri 2 children during the Covid-19 pandemic in Takalar Regency.